How strict is the correlation between STIM1 and Orai1 expression, puncta formation, and I(CRAC) activation? - Gwozdz, Tomasz (American Physiological Society, 2008)
Stromal interaction molecule 1 (STIM1) and Orai1 have been identified as crucial elements of the store-operated Ca(2+) entry (SOCE) pathway, but the mechanism of their functional interaction remains controversial. It is now well established that, upon depletion of the stores, both molecules can accumulate and colocalize in specific areas (puncta) where the endoplasmic reticulum comes in close proximity to the plasma membrane. Some models propose a direct interaction between STIM1 and Orai1 as the most straightforward mechanism for signal transduction from the stores to the plasma membrane. To test some of the predictions of a conformational coupling model, we assessed how tight the relationships are between STIM1 and Orai1 expression, puncta formation, and SOCE activation. Here we present evidence that STIM1 accumulates in puncta equally well in the presence or absence of Orai1 expression, that STIM1 accumulation is not sufficient for Orai1 accumulation in the same areas, and that normal Ca(2+) release-activated Ca(2+) current (I(CRAC)) can be activated in STIM1-deficient cells. These data challenge the idea of direct conformational coupling between STIM1 and Orai1 as a viable mechanism of puncta formation and SOCE activation and uncover greater complexity in their relationship, which may require additional intermediate elements.